1957
DOI: 10.1021/ie50574a043
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Cyanogen

Abstract: Stability of CyanogenCyanogen is stable enough to be handled in the laboratory and to be stored and shipped in Monel or stainless steel cylinders 1 he word "stability," as applied to a chemical compound, is a broad term. It denotes a resistance to one or more of several different kinds of possible behavior, such as polymerization, decomposition, and chemical reaction under a variety of conditions, such as heat, pressure, addition of reagent, or mechanical shock. To be meaningful, the word must be limited in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1959
1959
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Cyanogen contains a high latent energy, of the same order as that of acetylene (208), which can be released explosively when the compound reacts with oxidizing agents such as fluorine (120), chlorine monoxide (5), and ozone (178), or when a mixture of cyanogen and air is subjected to a spark (42). Although an explosion hazard exists with cyanogen, the pure material has been stored and shipped in stainless-steel cylinders with no reported mishaps (208). It has also been used safely in numerous reactions other than oxidations.…”
Section: Stability Of Cyanogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyanogen contains a high latent energy, of the same order as that of acetylene (208), which can be released explosively when the compound reacts with oxidizing agents such as fluorine (120), chlorine monoxide (5), and ozone (178), or when a mixture of cyanogen and air is subjected to a spark (42). Although an explosion hazard exists with cyanogen, the pure material has been stored and shipped in stainless-steel cylinders with no reported mishaps (208). It has also been used safely in numerous reactions other than oxidations.…”
Section: Stability Of Cyanogenmentioning
confidence: 99%
“…A comprehensive study was recently made by Welcher, Berets, and Sentz (208) on the stability of pure cyanogen to heat, pressure, chemical additives, and severe mechanical shock. They found that pure cyanogen was unchanged after 18 to 23 days at 65°C.…”
Section: Stability Of Cyanogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The heat of formation of cyanogen is extremely high (Pauling et al, 1939), but cyanogen is unexpectedly stable (Welcher et al, 1957), also, against air or oxygen. No explosion or detonation was experienced during the experiment, even when it was mixed with nitrogen dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…When aqueous potassium or sodium cyanide solution is poured onto cupric sulfate powder, cyanogen is evolved (Brauer, 1963; Welcher et al, 1957;Hahn and Leopold, 1935). This reaction can be written as follows:…”
mentioning
confidence: 99%